Penerapan Metode Direct Instruction dalam Meningkatkan Keterampilan Seni Henna Motif Flora bagi Anak Tunarungu di SKH Negeri 01 Pandeglang - Ishna Nahwal Aulia; Toni Yudha Pratama; Yuni Tanjung Utami (Lembaga Yasin AlSys, 2025)
This study is motivated by the limited research on the application of the direct instruction method to enhance floral henna art skills, despite the significant impact such skill development can have on the vocational abilities of deaf students, aligned with their individual interests and talents. The objective of this research is to improve the henna art makeup skills of deaf students through the application of the direct instruction method. A quantitative approach was employed using an experimental one-group pretest-posttest design, involving four participants selected through purposive sampling. Data were collected via performance tests and analyzed using the Wilcoxon signed-rank test. The analysis yielded a Thitung value of 10, which is greater than Ttabel = 0 at a 0.05 significance level (N=4), thus rejecting H₀. This indicates that the direct instruction method has a significant effect on improving floral henna art skills in deaf students. These findings support the theory that vocational skill development should align with students’potential, interests, and talents. The study concludes that direct instruction is effective in enhancing vocational skills among deaf students in the field of henna art. The implications include theoretical contributions to special education research and practical benefits for policy formulation, cosmetology skills training, and the development of inclusive vocational programs. This research also opens opportunities for further studies on applying similar methods to other relevant skill areas.